AN INVESTIGATION OF THE UTILISATION OF ENGLISH IN THE INTERNSHIP PROGRAMS AMONG THE CADETS OF NUSANTARA MARITIME ACADEMY - Muhammad Arinal Rahman; Moch. Nurdin (Akademi Maritim Nusantara, 2023)
This study aims to examine the utilisation of the English language within the context of the internship programme for maritime cadets, utilising interviews and observations as primary data collection methods. This qualitative research endeavour seeks to offer valuable insights into the role of English language in the internship program for maritime professionals. The findings of this study have made significant contributions to the improvement of language training programmes, communication protocols, and overall safety and efficiency in maritime internship settings. The empirical evidence indicates that possessing a strong command of English is essential for successfully carrying out safety drills, ensuring smooth vessel navigation and engine maintenance, fostering intercultural comprehension and efficient collaboration, and overseeing documentation procedures in port operations. The study places significant emphasis on the necessity of efficient language instruction, the resolution of language-related obstacles, and the facilitation of intercultural dialogue in order to adequately equip maritime academies and internship programs for fruitful internships and prospective careers as skilled and capable seafarers.